فعالية برنامج إثرائي يستند إلى التعليم المبرمج لتنمية مهارات القراءة للتلاميذ منخفضي التحصيل (Journal of Faculty of Education, 2021)
This study aimed to design a program based on programmed education for the development of reading skills for low-achievers. The study based on the semi-experimental method. The sample consisted of 12 low-achievment students from fourth grade. The sample was divided into two groups: a control group of 6 students students and an experimental group consisting of students. The study used the scale of socio-economic level of the family, and the scale of reading skills whereby the two scales were applied on the two groups.The results showed that the program, which bases on the programmed education is very effective as an educational tool. The study recommended that more studies be conducted on enrichment programs for low achievers at different age levels
Keywords: برنامج إثرائي; التعليم المبرمج; مهارات القراءة; منخفضي التحصيل